2013
DOI: 10.1002/da.22052
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized-Controlled Trial of an Intervention to Improve Antidepressant Adherence Among Latinos With Depression

Abstract: This initial trial of META demonstrated feasibility and promising effects for improving antidepressant adherence. Some effects on depression were also observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…The significantly larger effect size of Solomon et al, 32 which reported a continuous measure, created heterogeneity that led to nonsignificant results. Similar limitations occurred in the in-person and group analyses in which Interian et al 19 and Holstad et al 26 also had larger effect sizes. It is important to clarify the efficacy of different MI delivery modes 36 since they could improve MI's cost-effectiveness and reach among populations with access barriers.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…The significantly larger effect size of Solomon et al, 32 which reported a continuous measure, created heterogeneity that led to nonsignificant results. Similar limitations occurred in the in-person and group analyses in which Interian et al 19 and Holstad et al 26 also had larger effect sizes. It is important to clarify the efficacy of different MI delivery modes 36 since they could improve MI's cost-effectiveness and reach among populations with access barriers.…”
Section: Discussionmentioning
confidence: 58%
“…This was due to the variability in adherence measures that required further stratification of the (26,32,50), continuous (27); mixed MI: continuous (15,25); fidelity assessment: categorical (22,24,27,28,30,32), continuous (15, 15, 17-20, 22, 25, 27, 28, 33); no fidelity assessment: categorical (21,23,26,29), continuous (29); fidelity-based feedback: categorical (28,30,33), continuous (15,18,20,33,51); no fidelity-based feedback: categorical (21-24, 26, 27, 29, 32), continuous (19,22,25,27,29,34) Background of counselors: nurses: categorical (23,26,28,29), continuous (15,20,28,29); psychologist: continuous (17)(18)(19); pharmacists: categorical (32); master level: categorical (22,24), continuous ...…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach may facilitate the implementation and sustainability of this intervention in real world settings. The possibility that some patients may be more open to discussing their [46][47][48] Our randomized trial study had several strengths, including a large cohort of minority subjects across several states and the use of both an objective as well as self-reported measure of medication adherence. While many of our patients had low incomes and educational attainment, they were all insured.…”
Section: Discussionmentioning
confidence: 99%